Genetic mapping of X linked ocular albinism: linkage analysis in British families. - Charles, S J (1992)
Genetic linkage studies were performed in 16 British families affected by X linked ocular albinism (XLOA) using RFLPs from the Xp22.3 region. Linkage was confirmed between the XLOA locus (OA1) and the loci DXS143 (dic56; Zmax = 15.90 at theta = 0.0, confidence interval (CI) 0-0.035), DXS85 (782; Zmax = 15.67 at theta = 0.04, CI = 0.007-0.11), and DXS237 (GMGX9; Zmax = 12.65 at theta = 0.08, CI = 0.03-0.17). Multipoint linkage analysis placed OA1 between DXS85 (782) and DXS237 (GMGX9) with odds exceeding 10(4):1 to give the map DXS85-(OA1,DXS143)-DXS237-XG-Xpter. OA1 lies close to DXS143 (dic56) but in the absence of recombinants the order of these loci could not be determined.